2016
DOI: 10.1007/s00289-016-1662-y
|View full text |Cite
|
Sign up to set email alerts
|

Double bond-functionalized POSS: dispersion and crosslinking in polyethylene-based hybrid obtained by reactive processing

Abstract: Polyethylene-based organic inorganic hybrids were prepared by one-step reactive melt mixing using a mono-functionalized nanofiller, i.e., allyl-heptaisobutyl-substituted polyhedral oligomeric silsesquioxane (1POSS) and a multi-functionalized octavinyl polyhedral oligomeric silsesquioxane (8POSS). The hybrids were also prepared in dicumyl peroxide (DCP) presence and morphological, spectroscopical and calorimetric analysis were carried out. Moreover, rheological measurement and Sohxlet extraction were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This behaviour is usually reported for strong polymeric gels. 56,57 However, interestingly, the organogels flow at a lower value of strain than the hydrogels. The presence of f-HNT and f-HNT/CPT does not significantly influence the mechanical properties of the hydrogels in terms of the moduli and tan d values ( Fig.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…This behaviour is usually reported for strong polymeric gels. 56,57 However, interestingly, the organogels flow at a lower value of strain than the hydrogels. The presence of f-HNT and f-HNT/CPT does not significantly influence the mechanical properties of the hydrogels in terms of the moduli and tan d values ( Fig.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…28 In the spectra of the two reactants (seen Figure S1), there are 1619 cm À1 in SAA and 1628 cm À1 in MBA, corresponding to the C═C bond in the two chemicals. 29 However, the two peaks disappeared in the spectrum of the solid acid, indicating that the polymerization reaction was taken place and poly(MBA-SAA) was successfully prepared. The two reactants are soluble in water, while, the as prepared solid acid is insoluble in water, giving another evidence for the successful synthesis.…”
Section: Ir Analysismentioning
confidence: 99%
“…The authors reported that the resultant formation of a denser cross-linked network and better dispersion of the high-temperature resistant cage structure of DDSQ in the EPDM ablation resistance composites improved its mechanical and ablation performance [ 48 ]. Morici et al reported that a POSS type with vinyl groups was used to crosslink polyethylene with peroxides [ 49 ]. In this study, POSSs and PE were mixed with dicumyl peroxide (DCP) with one-step reactive melt mixing.…”
Section: Introductionmentioning
confidence: 99%